Contextualização da quantidade de movimento através de oficinas pedagógicas - Carvalho, Priscila Tibúrcio de (2021)
This dissertation was developed with the objective of contextualizing the theme of movement through pedagogical workshops (using experimental activities), elaborating and proposing a sequence of practical activities that enable the student's active participation in the teaching and learning process. The didactic strategy used aims to collect data through questionnaires, experimental activities and the interaction of students with the teacher who helps in the construction of knowledge. The practices carried out during the pedagogical workshop have a qualitative approach based on Ausubel's Theory of Meaningful Learning that allows observing the students' way of thinking and a quantitative approach using numerical data, relying on objective indices for the formation and construction of knowledge.